Sketching: A Method for Imagining Journalistic Tech. Issue 2 (7th February 2022) - Doherty, Skye; Worthy, Peter
Abstract: Internet-connected things, wearable computers and smart environments all promise new ways for publics to interact with information and with media professionals. In this environment, journalists and journalism educators have an opportunity to play a stronger role in designing stories and interactions that achieve social and democratic goals. Technical training, critical skills and entrepreneurial thinking are among the ways scholars and educators have grappled with this issue. In this article we add to these approaches, outlining a design-led initiative that introduces sketching as a method for exploring the use of technology in a journalistic context and imagining new possibilities. Rather than teach technological competency, we use sketching as a way to develop enterprise skills and foster creative thinking about how journalism might evolve in light of new and emerging technologies.